Implementation SEO and SEM to Enhance Brand Awareness and Consumer Loyalty - Rozaliana, Rozaliana; Azzahari, Muhammad; Khaldun, Ibnu (Journal of Artificial Intelligence and Software Engineering, 2025)
The development of digital technology has changed the way micro, small, and medium enterprises (MSMEs) market their products and build relationships with consumers. Digital marketing is one of the main strategies in increasing brand awareness and consumer loyalty. This study aims to analyze the effectiveness of digital marketing strategies in increasing brand awareness and consumer loyalty. The research methods used are literature studies and surveys of consumers who actively use digital platforms to interact with brands. The results of the study show that effective digital marketing strategies, such as the use of social media, content-based marketing, and service personalization, can increase brand awareness and build strong loyalty in consumers. By utilizing Search Engine Optimization (SEO),    Search Engine Marketing (SEM), and influencer marketing techniques, MSMEs can reach target markets more widely and effectively. These findings underline the importance of the role of digital marketing in the era of digital transformation that continues to grow. Therefore, an integrated and sustainable digital marketing strategy is needed to increase the company's competitiveness and maintain customer loyalty.